Analisis Deiksis pada Novel “Rembulan Tenggelam Di Wajahmu” Karya Tere Liye Serta Pemanfaatannya pada Materi Ajar Teks Novel - Arneta Destria Kirana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Deixis is a word that has a referent or reference that changes depending on who is speaking and the context of the conversation. Deixis can also be useful in direct or verbal communication activities. Examples of the benefits of deixis in indirect communication can be realized in literary works in the form of novels. In connection with the research to be conducted, the researcher chose the novel Rembulan sinks in your face as the research subject. Therefore, this research wants to examine the types, forms and functions of deixis as well as the use of deixis in the novel "Rembulan sinks on your face" by Tere Liye for Indonesian language learning. The data in this research are dialogues containing deixis in the novel Rembulan sinking on your face by Tere Liye, which was published in December 2006 with 400 pages. The data analysis technique used in the research is a qualitative descriptive method. Based on the research that the researchers have conducted in the novel Rembulan sinking in your face by Tere Liye, the author can conclude that there are several types of deixis in the novel Rembulan Tenggelam in Your Face, namely, place deixis, pointing deixis, persona deixis, time deixis, and social deicsis.